A Phase IV Study of the Safety and Efficacy of CinnoPar® in Iranian Patients with Osteoporosis - Ahmadreza Jamshidi; Farhad Gharibdoost; Sima Sedighi; Asghar Hajiabbasi; Amir-Hossein Salari; Alireza Khabbazi; Peyman Mottaghi; Ahmad Tahammoli Roudsari; Mehrdad Aghaei; Irandokht Shenavar Masooleh; Araz Sabzvari; Nassim Anjidani (Journal of Osteoporosis, 2021)
The safety of teriparatide has been studied in various phase III and phase IV trials. However, a postmarketing study of the biosimilar of teriparatide, CinnoPar®, has not been conducted on Iranian patients. This was a phase IV study conducted on osteoporotic patients who received an Iranian teriparatide biosimilar with a dose of 20 μg daily. The primary outcome of this study was to monitor for adverse events (AEs). Effectiveness as the secondary outcome was measured using the EQ-5D quality-of-life questionnaire and back pain Visual Analogue Scale (VAS) score. Among 193 analyzed patients between September 2015 and March 2019, the most common AEs were hypercalcemia (4%), nausea, and pain (3%). No deaths, serious AEs, or other significant AEs occurred in this study. The mean EQ-5D scores decreased after the course of the treatment from 2.3 ± 0.66 at the baseline to 2 ± 0.66. The mean back pain VAS scores also decreased from 4.9 ± 3.6 at baseline to 1.8 ± 2.1 at the end of the study. Both changes were statistically significant (p<0.001). Consistent with the findings of previous studies and the drug monograph, no new safety concern was observed with this biosimilar teriparatide, and the drug was effective based on the VAS score and EQ-5D in osteoporotic patients.